Morphological and histomorphometrical study of the Sacculus rotundus at different postnatal ages in indigenous rabbit: A. G. Al-Haaik and F. J. Al-Saffar - Al-Haaik, A. G. (The Iraqi Journal of Veterinary Medicine, 2017)
Current investigation was carried out to explore structural developmental changes of the acculus rotundus in indigenous rabbits at different postnatal ages. To conduct that, morphological, histological and morphometrical approaches were employed on 24 rabbits at ages one, ten, fifteen and forty days. The findings indicated that in one day kits, the Sacculus rotundus cannot recognized with the naked eye but in the next advanced ages it appeared as expanded pear-like structure situated at the end of ileum. It opened into the 2nd gyrus at the base of cecum by saccorotundocecal orifice. Because it extends for 1-2 millimeters inside the lumen of the cecum, an annular ridge formed encircles the site of this opening. Length and width of SR was increased significantly by age progression. The main four layers of the alimentary canal were presented in the wall structure of Sacculus rotundus but with apparent variations in its structural constituents and dimensions. Two types of epithelia were recognized in its mucosa, villus epithelium and follicular associated epithelium. The lamina propria was very thick and full of well-developed nodular and diffuse lymphoid tissue alongside the whole circumference of its wall even in the newly born kits. In conclusion, the SR might be considered as primary lymphoid organ in rabbit.